Long-term outcomes of intravenous drug use associated infective endocarditis: a contemporary 20-year study. (14th October 2021) - Khan, I; Brookes, E; Santamaria, J; Wilson, A; Darby, J; Newcomb, A
Abstract: Introduction: Intravenous drug use (IVDU) associated infective endocarditis (IE) is a clinically challenging case. Not only can the natural history of IE in the IVDU population be significantly different, making detection a diagnostic dilemma, additional social factors associated with this population can drastically change management, including suitability for surgery or long-term intravenous access for antibiotics Furthermore, the rates of IVDU are increasing globally, leading to increasing incidence of IVDU associated IE. Purpose: With a lack of clear mangement guidelines for IVDU associated IE, our study assesses the differences in presentation, management and long-term prognosis of IE between the IVDU population and the non-IVDU population to help guide future care. Methods: This is an observational cohort study on a prospectively collected database of 350 patients treated for IE at our centre between 1999 and 2015. Patients were followed-up until death or January 2021. The primary outcome was all-cause mortality. Continuous variables were compared using unpaired t-test. Categorical variables were compared using Chi-square test when sample size was >5 or Fisher's exact test when sample size was ≤5. Long-term survival data was analysed using Kaplan-Meier survival curves. Results: The IVDU population was younger, more likely to have concurrent infections and other substance use, while the non-IVDU population was older with a higher level of overall comorbidity. IVDU patients were more likely to become reinfected (p-value=0.034) but had better long-term survival compared to the non-IVDU population (p<0.001). Survival estimates at 15-years were 64.98% (95% CI: 50.94–75.92%) for the IVDU population compared to 26.67% (95% CI: 19.76–34.05%) for the non-IVDU population (p-value<0.0001). Conclusion: Despite having higher levels of reinfection, IVDU patients have better long-term outcomes of IE compared to non-IVDU patients. Therefore, IVDU patients should not have blanket restrictions on the management they are offered unless the individual has clear contraindications to a particular therapy. Funding Acknowledgement: Type of funding sources: None.